Exploring the Dynamics of Maqashid Performance in Indonesian Islamic Banking - Nastiti, Ari Sita (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This study investigated the factors influencing the performance of Islamic banks in Indonesia by utilizing the Maqasid Sharia Index (MSI), specifically designed to assess Islamic bank performance in accordance with maqasid sharia principles. The sample sample was drawn from 57 data points gathered from 12 Islamic commercial banks registered with the Financial Services Authority (Otoritas Jasa Keuangan-OJK) from 2016-2020. Employing a quantitative approach, the study conducted data analysis through multiple linear regression. The results revealed that temporary shirkah funds and Islamic intellectual capital had a significant negative impact on MSI, while Islamic corporate governance exhibited a notably positive effect. This empirical investigation provides valuable insights into the determinants of Islamic bank performance in Indonesia, thereby contributing to the existing body of Islamic banking literature and offering practical implications for enhancing alignment with maqasid sharia through strategic resource optimization. The findings highlight the critical importance of reinforcing Islamic corporate governance and Islamic intellectual capital to enhance the performance of Islamic banks. Furthermore, expanding the scope of research to broader contexts could improve the generalizability of these findings.============================================================================================================ABSTRAK - Eksplorasi Dinamika Kinerja Perbankan Syariah Indonesia dengan Indeks Maqasid. Penelitian ini bertujuan untuk mengkaji determinan yang mempengaruhi kinerja perbankan syariah di Indonesia melalui pendekatan Maqasid Sharia Index (MSI). MSI khusus dikembangkan secara khusus untuk mengukur kinerja bank syariah agar lebih akurat karena mengakomodir prinsip-prinsip maqasid syariah. Sampel penelitian diambil dari 57 poin data dari 57 bank umum syariah yang terdaftar di Otoritas Jasa Keuangan (OJK) periode 2016-2020. Penelitian ini menggunakan pendekatan kuantitatif dimana data dianalisis melalui regresi linier berganda. Hasil kajian menunjukkan bahwa dana syirkah temporer dan modal intelektual syariah secara signifikan berpengaruh negatif terhadap MSI, sebaliknya tata kelola perusahaan syariah menunjukkan pengaruh positif yang signifikan. Hasil ini memberikan gambaran tentang determinan kinerja perbankan syariah di Indonesia, sehingga berkontribusi pada literatur perbankan syariah yang ada dan menawarkan implikasi praktis untuk meningkatkan kesesuaian dengan maqasid syariah melalui optimalisasi sumber daya strategis. Temuan ini menekankan pentingnya memperkuat tata kelola perusahaan syariah dan modal intelektual syariah untuk meningkatkan kinerja bank syariah. Untuk dapat meningkatkan generalisasi temuan ini, diperlukan kajian lebih lanjut dalam konteks yang lebih luas.